The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.compscitech.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Damage initiation and structural degradation through resonance vibration: Application to composite laminates in fatigue

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractThe definition of failure is fundamental to the characterisation of fatigue strength of components and structures and is often expressed as a percentage of stiffness degradation. This article proposes a new method to capture damage initiation and structural degradation during a fatigue test, by exploiting resonance vibrations. The method entails monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 24 publications
2
32
0
Order By: Relevance
“…The self-heating temperature distribution depends directly on the applied stress, and is usually non-uniform due to the non-uniform stress distribution during cyclic loading (see Figure 2). Similar temperature distributions can be found, e.g., in [24,25], while a typical distribution during cyclic loading is presented in [20,26,27,28] for tensile, in [29] for compressive, and in [20] for shear loading, respectively. The dependency between these two quantities is as follows: the higher the stress concentration, the higher the self-heating temperature.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…The self-heating temperature distribution depends directly on the applied stress, and is usually non-uniform due to the non-uniform stress distribution during cyclic loading (see Figure 2). Similar temperature distributions can be found, e.g., in [24,25], while a typical distribution during cyclic loading is presented in [20,26,27,28] for tensile, in [29] for compressive, and in [20] for shear loading, respectively. The dependency between these two quantities is as follows: the higher the stress concentration, the higher the self-heating temperature.…”
Section: Introductionsupporting
confidence: 75%
“…As was previously observed, the highest values of the self-heating temperature are noticeable in the region of the highest stress concentrations, which often indicate the locations of initiation of fracture. This property can be used for damage detection in polymeric and PMC structures, which were reported in numerous studies [1,24,128,129,130]. An overview on the self-heating based diagnosis of such structures is extended in further sections.…”
Section: Literature Review On the Self-heating Effectmentioning
confidence: 92%
“…This phenomenon was highlighted and initially studied by the author in [13], where the relation between the self-heating temperature distribution and formation of a macrocrack was shown. Later, the authors of [14,15] confirmed the relation of damage formation and evolution with changes in the self-heating temperature distribution.…”
Section: Introductionmentioning
confidence: 92%
“…In VT methods, the excitation is also possible by subjecting a tested structure to mechanical vibrations with a low-range frequencies. Such an approach was reported in several studies [ 13 , 14 ]. In this case, depending on the materials condition and properties, three mechanisms are possible: energy dissipation due to friction, micro-plasticization, and thermoviscoelasticity [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 97%
“…These distributions coincide with modal shapes of vibration, when the tested structures were loaded on their natural frequencies of vibration. The self-heating effect in polymeric structures was used for thermal excitation in several studies (see e.g., [ 13 , 20 , 21 ]), however, in the first case, the self-heating effect was just a tool for observation of an initiated crack, while, in the two latter cases, the excitation in the ultrasonic frequency range was performed.…”
Section: Introductionmentioning
confidence: 99%